PATIENT AUTONOM Y IN MEDICAL TREATMENT : THE MALAYSIAN PERSPECTIVE - CHE NGAH, Anisah; YUSOF, Yuhanif; ZAINUDIN, Tengku Noor Azira Tengku; SHAIR MOHAMED, Mohd. Akram; FARIHA RAMLAN, Wan Nur (MEDECINE LEGALE DROIT MEDICAL, 2025)
Since the olden days, people have put their faith and trust in medical practitioners, as they believe in the saying that “doctor knows best”. This has been termed as beneficence or medical paternalism where the doctor is like a parent figure acting in the best interest of the patient who adopts the role of a child. However, patients have become more aware of their rights and are more active in making decisions for themselves, opposing the idea of paternalism. Gone are the days where a patient leaves everything to the doctor, especially in Western countries, which value self-determination and individual rights. In the Eastern part of the world, the trend is leaning towards patient autonomy. The focus of this paper is to consider whether patient autonomy in medical treatment is recognized in Malaysia. To answer the question, content analysis on relevant cases, statutes and policies has been carried out. It is observed that recognition for patient autonomy in Malaysia is only through legal means. There are several legal cases relating to issues of consent, advice and disclosure of information where the courts in general favour patient autonomy. However, recognition of patient autonomy through non-legal means is minimal. This is considered unfortunate because access to courts is expensive and available to only a portion of the society.